Uncover The Consumer Preferences in Jakarta Satellite Cities after Pandemic - Rahmawati, Dwi (SEIKO : Journal of Management & Business, 2023)
This study aims to understand the impact of the Covid-19 on consumer preferences in Jakarta Satellite Cities: Bogor, Depok, Tangerang, and Bekasi. In this pandemic situation, people's daily lives were disrupted by quarantine, so it significantly changes people's lifestyles. The methodology of this study is by applying a quantitative research method through questionnaires from across the Bodetabek area. The overall number of respondents in this research is 116, with 58 questions. This study shows that online streaming is the most preferred activity when people seem worried about going outside. Furthermore, the pandemic affects people's financial condition. The majority of people show that their income is decreased when the expenses and savings are increased. So, they are more aware and look for ways to save money when shopping rather than buying unnecessary things. The change in the financial condition is affecting the buying behaviour of the people. People tend to buy food and beverages as their priority in this pandemic Covid-19 situation rather than buying fashion stuff. The result of this study can be helpful for Consumer Goods Company or UMKM to understand consumer preferences so that they can be adapted to the change of consumer preferences in the Covid-19 situation. Keywords: Consumer Preferences, Covid-19, Quantitative Method, Buying Behavior